2017
DOI: 10.1007/s10549-017-4161-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher densities of Foxp3+ regulatory T cells are associated with better prognosis in triple-negative breast cancer

Abstract: In summary, the combination of high densities of intra-tumoural Tregs, CD8 T cells and CD20 B cells represents a favourable prognostic panel in TNBCs. These data also indicate new avenues for further investigation on the interaction between immune cell types within the tumour microenvironment and highlight the potential of Treg density and localisation within tumours to affect clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 65 publications
9
104
1
Order By: Relevance
“…In contrast to our observations, Yeong et al reported that a high density of intratumoral FOXP3+ cells was associated with longer overall survival but not with stromal infiltration. 36 In our study, lower TILs scores were observed in the AR+ subclass of TNBC, which is considered to be a prime candidate for anti-androgen and CDK4/6 inhibition therapies. 37,38 However, no differential expression of TILs or various immune cell subtypes was observed with regard to subclassification of TNBC into basal-like and non-basal-like groups.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In contrast to our observations, Yeong et al reported that a high density of intratumoral FOXP3+ cells was associated with longer overall survival but not with stromal infiltration. 36 In our study, lower TILs scores were observed in the AR+ subclass of TNBC, which is considered to be a prime candidate for anti-androgen and CDK4/6 inhibition therapies. 37,38 However, no differential expression of TILs or various immune cell subtypes was observed with regard to subclassification of TNBC into basal-like and non-basal-like groups.…”
Section: Discussionsupporting
confidence: 48%
“…In contrast to our observations, Yeong et al . reported that a high density of intratumoral FOXP3+ cells was associated with longer overall survival but not with stromal infiltration . In our study, lower TILs scores were observed in the AR+ subclass of TNBC, which is considered to be a prime candidate for anti‐androgen and CDK4/6 inhibition therapies .…”
Section: Discussionmentioning
confidence: 42%
“…Furthermore, increased numbers of CD4+ FoxP3+ regulatory T cells were associated with an unfavorable prognosis, however, results were controversial as other studies observed opposite results . The complexity of the CD4+ FoxP3+ population was also elucidated in colorectal cancer, where instability of FoxP3 was associated with less immunosuppressive T‐cell phenotypes …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increased numbers of CD4+ FoxP3+ regulatory T cells were associated with an unfavorable prognosis, [19][20][21] however, results were controversial as other studies observed opposite results. 22,23 The complexity of the CD4+ FoxP3+ population was also elucidated in colorectal cancer, where instability of FoxP3 was associated with less immunosuppressive T-cell phenotypes. 24 In addition, CD68+ TAMs, commonly identified by the expression of CD163, CD206, or CD204, 25 also sustain the development and progression of many tumors, including oropharyngeal cancer, by suppressing the cytotoxic activity of CD8+ T cells, and promoting angiogenesis and tumor cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative multiplex immunofluorescence (QmIF) was performed using an Opal Multiplex Immunohistochemistry (IHC) kit (PerkinElmer, Inc., Waltham, MA, USA) as previously described [12][13][14][15][16][17][18][19][20][21][22] , on FFPE tissue sections processed according to the standard IHC protocol described above. The slides were first incubated with primary antibodies against CD3, CD8, CD103, Glypican, Ecadherin and PD-1 and the nuclei were counterstained with DAPI (Table 2), before incubation with fluorophore-conjugated tyramide signal amplification buffer (PerkinElmer, Inc., Waltham, MA, USA).…”
Section: Quantitative Multiplex Immunofluorescence (Qmif)mentioning
confidence: 99%